Cultures in Conflict Religion, History and Gender in Northern Europe c. 1800-2000 - Maurits, Alexander; Sidenvall, Erik; Ljungberg, Johannes (Peter Lang International Academic Publishing Group, 2021)
This book includes studies of main conflict areas in modern Western societies where religion has been a central element, ranging from popular movements and narratives of opposition to challenges of religious satire and anti-clerical critique. Special attention is given to matters of politics and gender. With this theme, it provides a useful guide to conflict areas in modern European religious history.